2014
DOI: 10.1142/s1793292014300023
|View full text |Cite
|
Sign up to set email alerts
|

A Review of Metal Oxide Composite Electrode Materials for Electrochemical Capacitors

Abstract: With the emerging technology in the 21st century, which requires higher electrochemical performances, metal oxide composite electrodes in particular o®er complementary properties of individual materials via the incorporation of both physical and chemical charge storage mechanism together in a single electrode. Numerous works reviewed herein have identi¯ed a wide variety of attractive metal oxide-based composite electrode material for symmetric and asymmetric electrochemical capacitors. The focus of the review … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
67
0
2

Year Published

2015
2015
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 166 publications
(77 citation statements)
references
References 126 publications
(191 reference statements)
0
67
0
2
Order By: Relevance
“…1 In conventional capacitors, the separator used is called dielectric, which prevents the moving of charges between the electrodes. Supercapacitors comprise 4 major components, namely, current collector, electrode materials that consist of electroactive materials, electrolyte, and the separator.…”
Section: Introductionmentioning
confidence: 99%
“…1 In conventional capacitors, the separator used is called dielectric, which prevents the moving of charges between the electrodes. Supercapacitors comprise 4 major components, namely, current collector, electrode materials that consist of electroactive materials, electrolyte, and the separator.…”
Section: Introductionmentioning
confidence: 99%
“…However, the fatal 2 drawbacks of single metal oxide were low electronic conductivity and short cyclic lifetime. It was reported that their composited or binary metal oxides had better capacitive behavior compared with the single metal oxides [7,8], due to their variable oxidation states and high electronic conductivity [9]. Hence, binary metal oxide electrodes might be the next-generation high-performance electrode materials for electrochemical energy storage devices.…”
Section: Introductionmentioning
confidence: 99%
“…Supercapacitors have advantages over well-known electrochemical storage devices, such as large power capability and long cycle life (up to 10 6 cycles) [1,2].…”
Section: Introductionmentioning
confidence: 99%